Open Broadcaster Software Assisted Learning Media in Hybrid Learning - Raharjo, Makmum; Erna Retna Safitri; Ardi Saputra (Universitas Pendidikan Ganesha, 2023)
Obstacles often found by teachers in implementing hybrid learning include internet connection and student access to participate in synchronous learning, which results in ineffective learning. The development of learning media assisted by Open Broadcaster Software (OBS) can be a solution to solve this problem. This study aims to analyze the practicability and effectiveness of OBS-assisted learning media in hybrid learning. In this case, the method applied is Research & Development (R and D) by applying the ADDIE model steps. The technique of collecting data for this research is in the form of questionnaires and tests. The research data collection was carried out using a checklist questionnaire in the form of a Likert scale. Data analysis techniques used qualitative and quantitative descriptive statistical analysis. Based on the practicality test analysis, a score of 90.0% was obtained, which means that the media developed is in the practical category. The pre-test and post-test results obtained an N gain value of 0.75. moderate category. It was concluded that OBS-assisted learning media was effectively used in learning. OBS-assisted learning media can help students learn.